Kultur In Vitro Endosperma, Protokol yang Efisien untuk Mendapatkan Tanaman Triploid secara Langsung - Lazarus Agus Sukamto (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2010)
In Vitro Culture of Endosperm: An efficient protocol topropagate triploid plants directly. L. Agus Sukamto.Triploid plants are very vigorous and beneficial since theygenerally produce seedless fruits, bigger flowers, and producemore volume of wood than the diploid counterparts.The triploid plants can be produced by crossing diploid andtetraploid plants, but this method is cumbersome and takesa long time. In vitro culture of endosperm is an alternativemethod to produce triploid plants directly. The success ofendosperm culture is dependent on many factors, such asmaturity of endosperm, presence of the zygotic embryo, culturemedium, growth regulators, browning, culture period,an plant species. Generally, a mature endosperm needs aninitial association with an embryo to induce cell divisions,while proliferation of an immature endosperms is notdependent on the embryo. Endosperm of most parasiticangiosperms shows direct organogenesis without callusformation. Plants produced from endosperm culture aregenerally triploid, although some plants possess differentploidy levels.